A Question of Consensus : The Doctrine of Assurance after the Westminster Confession - Master, Jonathan (Book collections on Project MUSE., 2015)
From the very earliest days after its completion in 1646, the Westminster Confession's position on assurance has been a subject of controversy. In this exciting new work, Jonathan Master considers the Westminster Confession's statements on assurance as a position of consensus among a diversity of viewpoints. Master traces how from this one position, the idea was expanded and modified--even by the document's own authors!--just years after its reception, in very distinct ways. Each of these expansions on what was intended to be a consensus document forms the basis for later traditions regarding assurance within the Reformed and Evangelical traditions. To date, few studies have examined these expansions as a united whole, and Master's work highlights the ways in which the streams of thought flowing out of Westminster are as important as those flowing into it, raising as they do questions about confession and doctrinal freedom in the growing Reformed tradition.